ANALISIS KEBAKARAN HUTAN DAN LAHAN DARI SISI FAKTOR PEMICU DAN EKOLOGI POLITIK - Adi Subiyanto (Jurnal Manajemen Bencana (JMB), 2020)
Forest fires are seen as a technical problem so that their resolution is only a technological measure. This study aims to find answers to the question of forest fires. What are the factors that trigger forest fires, the correlation between trigger factors, and explain that the human is the leading cause of forest fires? The method used is mixed methods, combining quantitative analysis and qualitative descriptive. Hot weather and dry ecosystem conditions do not cause fires, not a causality relationship. The leading cause of forest fires in Indonesia is by human activities. The importance of a political ecology approach to explaining the linkages between forest fires and the role of actors, both local and regional/global in managing the environment.